Risk Factors for Stunting in Toddlers in the Public Health Center Working Area Embo Jeneponto, South Sulawesi - Rosdiana Syakur; Musaidah Musaidah Musaidah; Nur Handayani (Postgraduate, University of Mataram, 2023)
Stunting is still a nutritional problem in Indonesia, including in South Sulawesi. The impact of stunting is very broad, starting from the individual, family, community, and country levels. This study aims to analyze the risk factors for stunting incidents in the Embo District Health Center Work Area, Jeneponto. The type of research used in this research is observational with a